Tug-of-war - Luper, Eric (New York : Scholastic Inc., 2016)
When Mason and Hannah find a tiny yellow Labrador named Nilla out by the old mill, Hannah is dying to keep her. But Mason isn't sure that's a good idea.
4.2
3-6
Keywords: Dogs -- Fiction; Family life -- Fiction; Dogs -- Fiction; Family life -- Fiction